The challenges facing the music industry in Zimbabwe: a case of the National Arts Council of Zimbabwe - Butete, Victoria B. (Midlands State University, 2015)
This study sought to determine ways of promoting music by looking at the challenges facing the structures in the music industry. In this study 25 research participants were used comprising two National Arts Council of Zimbabwe officials, three musicians and twenty audience members. Interviews and questionnaires were used as data collection instruments while content analysis was used to make sense out of secondary sources as well as the data gathered. The results of the study show that lack of music business education and training is the major challenge facing the industry. The study also found that the music industry contributes significantly to economic development of Zimbabwe both directly and indirectly, hence the development of the music industry can be used to develop the economy and to help achieve the Millennium Development Goals (MDGs). Further study should be carried out on the challenges facing the music industry to determine the needs of the key stakeholders so as to inform policy formation and come up with different ways of promoting the industry. It is recommended that there is need for communication between the government, sister ministries, the NACZ, all the music industry stakeholders and other interested parties. The study should be replicated to see if the same conclusions can be reached across Zimbabwe to build a strong case for the development of the music industry through education and training.